LEKSIKON MAKANAN TRADISIONAL BETAWI: KAJIAN ETNOLINGUISTIK - Nisa, Chairun; Valencia, Berliana Intan; Baehaqie, Imam (Jurnal PENEROKA, 2025)
This study aims to identify the lexicon form along with the literal meaning and cultural meaning contained in the naming of typical Jakarta culinary made from coconut. The reason for this study was conducted because many typical Betawi foods use coconut as an ingredient. By combining ethnolinguistic theory to examine the relationship between language and culture in the naming of typical Betawi culinary. The focus of this study is how the lexical form and literal meaning of typical Jakarta food made from coconut. This study uses a qualitative descriptive method with an ethnolinguistic approach. A list of typical Jakarta food names along with descriptions of the food names are the subjects of this study. The findings of this study obtained 13 lexicons, each of which is categorized into 2 data categories of heavy food, 10 data categories of snacks, and 1 data category of drinks. An interesting fact in this study is that coconut-based culinary is dominated by the snack category, which shows that coconut is not only an ingredient but also has an important role in creating a variety of typical Betawi food that is rich in cultural meaning.